2009
DOI: 10.1021/ja804200v
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Versus Linear Isomers Produced by Reaction of the Methylidyne Radical (CH) with Small Unsaturated Hydrocarbons

Abstract: The reactions of the methylidyne radical (CH) with ethylene, acetylene, allene, and methylacetylene are studied at room temperature using tunable vacuum ultraviolet (VUV) photoionization and time-resolved mass spectrometry. The CH radicals are prepared by 248 nm multiphoton photolysis of CHBr 3 at 298 K and react with the selected hydrocarbon in a helium gas flow. Analysis of photoionization efficiency versus VUV photon wavelength permits isomer-specific detection of the reaction products and allows estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(170 citation statements)
references
References 85 publications
10
160
0
Order By: Relevance
“…In the CH + C 2 H 2 reaction, the cyclic C 3 H 2 product is primarily observed, in contradiction to previous calculations, which suggested that linear triplet propargylene (HCCCH) accounts for 90% of the product formation. New calculations 59 indicate that a somewhat higher production of the cyclic product (27%) should be expected, however, from these calculations together with D atom isotope studies, it was shown that subsequent H-atom assisted isomerization of the triplet propargylene is most likely responsible for the additional large conversion to the observed c-C 3 H 2 . Cyclic isomers are also observed for the reaction of CH with methylacetylene.…”
Section: In a Collaboration With David Osborn And Craig Taatjes Of Thmentioning
confidence: 94%
“…In the CH + C 2 H 2 reaction, the cyclic C 3 H 2 product is primarily observed, in contradiction to previous calculations, which suggested that linear triplet propargylene (HCCCH) accounts for 90% of the product formation. New calculations 59 indicate that a somewhat higher production of the cyclic product (27%) should be expected, however, from these calculations together with D atom isotope studies, it was shown that subsequent H-atom assisted isomerization of the triplet propargylene is most likely responsible for the additional large conversion to the observed c-C 3 H 2 . Cyclic isomers are also observed for the reaction of CH with methylacetylene.…”
Section: In a Collaboration With David Osborn And Craig Taatjes Of Thmentioning
confidence: 94%
“…A small amount of N 2 is added to the main flow to quench any vibrationally excited CH radicals. 5 All flows are metered using calibrated mass flow controllers. In our experiment, the photolysis fluence is typically ~15 mJ/cm 2 in a ~20 ns pulse duration inside the flow tube.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…When the ions are time-tagged on detection, secondary chemistry can be identified. 44 Comparing measured spectra to reference absolute ionization cross-sections for each individual isomer can ultimately provide product branching ratios.…”
Section: Introductionmentioning
confidence: 99%